2019
DOI: 10.1016/j.csbj.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computational Biochemistry for Elucidating Molecular Mechanisms of Nitric Oxide Synthase

Abstract: Nitric oxide (NO) is an essential signaling molecule in the regulation of multiple cellular processes. It is endogenously synthesized by NO synthase (NOS) as the product of L-arginine oxidation to L-citrulline, requiring NADPH, molecular oxygen, and a pterin cofactor. Two NOS isoforms are constitutively present in cells, nNOS and eNOS, and a third is inducible (iNOS). Despite their biological relevance, the details of their complex structural features and reactivity mechanisms are still unclear. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 186 publications
(275 reference statements)
1
10
0
Order By: Relevance
“…The residue Arg-375 is a key amino acid to regulate H 4 B which contributes to electron transfer and stability of dimer (Cinelli et al, 2020). Cofactor heme (HEM 901) is the catalytic centre that oxidizes L-arginine to L-citrulline, it also serves as an anchor and plays a key role in the electron transfer chain (Bignon et al, 2019). Additionally, it has been reported that Arg-260 and Gln-257 were the targeted residues of novel NO inhibitors (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The residue Arg-375 is a key amino acid to regulate H 4 B which contributes to electron transfer and stability of dimer (Cinelli et al, 2020). Cofactor heme (HEM 901) is the catalytic centre that oxidizes L-arginine to L-citrulline, it also serves as an anchor and plays a key role in the electron transfer chain (Bignon et al, 2019). Additionally, it has been reported that Arg-260 and Gln-257 were the targeted residues of novel NO inhibitors (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the hierarchy of numerical methods can all be developed to reproduce the biochemical processes in mechanotransduction. For example, quantum mechanics/molecular mechanics (QM/MM) computations, which fall under microscopic methods (subatomic scale, to be precise) and advances in probing the electron transfer process, can be applied to find reaction mechanisms of enzymes, like the activation of eNOS (endothelial nitric oxide synthase) as reviewed in Bignon et al (2019). Also, reactive force field MD (Senftle et al, 2016) simulations, which uses QM-trained force fields to mimic bond breaking and formation and have been extensively proved to be effective in capturing reaction pathways, can be applied to work out the chain reactions after the release of Ca 2+ initiated by mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…nNOS, eNOS and iNOS are the neurotype, endothelial type and inducible type of NOS, respectively. 38 Under normal physiological conditions, the mechanism of NO production, release, diffusion and inactivation is precisely regulated in the nervous system, which is mainly achieved by regulating the activation and deactivation of nNOS. 39 nNOS not only plays an important role in the nervous system, but is also distributed in gastric mucosal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%